Movement of Islamic Organization and Its Impact on Radical Perception with Supply Chain Management in the Digital Era - Sitti Jamilah Amin (International Journal of Supply Chain Management, 2020)
Abstract- An effectively formulated and properly executed Digital Supply Chain Strategy becomes a value driver for organisations. Modern communications and information technology are changing the nature of terrorism in Indonesia. The use of social media by the Islamic State (IS) is transforming the recruiting and contact mechanisms. This study examined the relationship amid anonymous sharing portal, supply chain management system, recruitment and radical perception with the mediating effect of communication. Islamic State is recruiting Indonesian Muslims to wage jihad (holy war or struggle) in Iraq and Syria through communication networks. IS previously used mainstream social media platforms such as Facebook, Twitter and YouTube, to achieve its political ends? After IS‘s social media accounts had been closed down by the authorities, communication shifted to the anonymous sharing portals. This article analyses the nature of IS‘s social media strategy and the impact it has had on radicalization and recruitment in Indonesia. The research method consist of analysing the themes and patterns of IS‘s social media presence. The IS seems to have developed an effective social media strategy given the number of Indonesian members undertaking the hijrah (jihad by emigration) to Syria and Iraq. The paper will answer a question on how the used of social media had effectively increased the members’ salafi-jihadist movement and utopian views of the establishment of a State which implemented Syariah Law.